Fumigant Effect of Essential Oils from Citronella (Cymbopogon nardus) and Lemongrass (Cymbopogon citratus) against pest Red Flour Beetle (Tribolium castaneum) - Dina Okta Tiana; Maria Heviyanti; Yenni Marnita (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
This study aims to determine the fumigant effect of citronella (Cymbopogon nardus) and lemongrass (Cymbopogon citratus) essential oils against the red flour beetle (Tribolium castaneum). This research was carried out at the Basic Laboratory of Samudra University and the Agrotechnology Laboratory of the Faculty of Agriculture, Samudra University, Langsa City, Aceh Province, which took place from February to March 2021. Using a non-factorial Completely Randomized Design (RAL). The results showed that the fumigant effect of citronella essential oil, treatment S5 (3.2% v/v) caused T. castaneum mortality of 93.75%, fumigant effect of lemongrass essential oil in treatment D5 (5.4% v/v). ) caused T. castaneum mortality of 92.5%. In the repellency test of citronella and lemongrass essential oils, treatments S5 and D5 (25%) were effective as repellents for T. castaneum at 24 hours after treatments.